2022
DOI: 10.3390/antiox11020315
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Localization of Kynurenine 3-Monooxygenase in the Brain: Challenging the Dogma

Abstract: Kynurenine 3-monooxygenase (KMO), a key player in the kynurenine pathway (KP) of tryptophan degradation, regulates the synthesis of the neuroactive metabolites 3-hydroxykynurenine (3-HK) and kynurenic acid (KYNA). KMO activity has been implicated in several major brain diseases including Huntington’s disease (HD) and schizophrenia. In the brain, KMO is widely believed to be predominantly localized in microglial cells, but verification in vivo has not been provided so far. Here, we examined KP metabolism in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…Inflammatory activation of IDO in peripheral cells will increase plasma levels of kynurenine and 3HK which enter the CNS by diffusion and by the amino acid transporter LAT-1 (SLC7A5) ( Sinclair et al, 2018 ; Figure 4 ). Kynurenine is then metabolized to kynurenic acid (in astrocytes) and quinolinic acid (in microglia and neurons) ( Figure 1 ), ( Guillemin et al, 2001 ; Sathyasaikumar et al, 2022 ) which leave the CNS slowly via the acidic amino acid transporter, blocked by probenecid ( Figure 4 ). Stimulation of macrophages by IFN-γ therefore increases the synthesis and release of quinolinic acid ( Heyes et al, 1992a ; Chiarugi et al, 2000 ; Guillemin et al, 2005a ; O’Connor et al, 2009a , b ; Garrison et al, 2018 ) which tends to accumulate in the CNS.…”
Section: An Integrated Kynurenine-cytokine Systemmentioning
confidence: 99%
“…Inflammatory activation of IDO in peripheral cells will increase plasma levels of kynurenine and 3HK which enter the CNS by diffusion and by the amino acid transporter LAT-1 (SLC7A5) ( Sinclair et al, 2018 ; Figure 4 ). Kynurenine is then metabolized to kynurenic acid (in astrocytes) and quinolinic acid (in microglia and neurons) ( Figure 1 ), ( Guillemin et al, 2001 ; Sathyasaikumar et al, 2022 ) which leave the CNS slowly via the acidic amino acid transporter, blocked by probenecid ( Figure 4 ). Stimulation of macrophages by IFN-γ therefore increases the synthesis and release of quinolinic acid ( Heyes et al, 1992a ; Chiarugi et al, 2000 ; Guillemin et al, 2005a ; O’Connor et al, 2009a , b ; Garrison et al, 2018 ) which tends to accumulate in the CNS.…”
Section: An Integrated Kynurenine-cytokine Systemmentioning
confidence: 99%
“…Of note, the production of KYNA occurs in astrocytes; however, 3-HK, QUIN, and AA are produced in microglia ( 11 ). Furthermore, a study conducted by Sathyasaikumar et al, found KMO only in microglia and neurons but not in astrocytes using isolated mouse cells ex vivo ( 12 ). Then, 3-HK and AA are degraded to 3-hydroxyanthranilic acid (3-HANA).…”
Section: Introductionmentioning
confidence: 99%
“…KMO, a mitochondrial enzyme belonging to the nicotinamide adenine dinucleotide phosphate hydrogen (NADPH)-dependent flavin monooxygenase family, operates with the flavin adenin dinucleotide cofactor and holds a central position within the KP metabolism (32). KMO is primarily present in peripheral tissues, macrophages, and monocytes, while in the nervous system, it is mainly concentrated in microglial cells (33). KMO catalyzes the transformation of KYN into neurotoxic compounds, notably 3hydroxykynurenine and QA, known for their brain excitotoxicity (34).…”
Section: Qa、3-haa and Kmomentioning
confidence: 99%